Diagnóstico de la gestión para la comercialización directa de ganado bovino en la parroquia Eloy Alfaro del cantón Chone - Corella Mejía, Iván Adolfo (2013)
This research was carried out in the state Santos, Javier, El potro, La Taberna and La Milagrosa these sites belongs to Zapallo, Eloy Alfaro of a town called Chone, it had diagnostics of the Cattle Marketing Management, investigating eight factors. We applied diagnostic tools such as: method of weighting factors, the creation of indexes and sub-indexes that evaluate the Marketing Management. The application of Kendall coefficient, determine that the level of acceptance between the experts obtaining W=0,704, being a positive result. The mathematical expressions determine the index of compliance of the Management of Marketing of cow cattle, taking a value of 0.611, which in the scale is in an intermediate position. Complying with the factors that influence in the Marketing Management, one of the problems that were settle in the distribution, obtaining a value of 0.304, while in an unfavorable situation, this score has been the lowest within the diagnostic perform to the factors that influence in the marketing management. With this results we take a step of the creation of an improvement plan, where they are defined measures affecting or eliminate the creation of a plan for improvement, where they are defined measures affecting or eliminate the shortcomings in the implementation of the marketing management, these measures are actions to be pursued, and for this is established the major responsible in each one of the aspects to perform within the plan for improvement.